ENHANCING EFL (ENGLISH AS FOREIGN LANGUAGE) STUDENT’S PUBLIC SPEAKING ABILITY THROUGH PRE-TEACHING VOCABULARY - Ramadhani, Putri (Universitas Methodist Indonesia, 2023)
The aim of this research is to investigate the effectiveness of pre-teaching vocabulary taught in the class by English lecturer towards the first semester students of Computer Informatics who are the users of English as Foreign Language (EFL students). The students are treated by pre-teaching vocabulary method in three stages they are introduction stage, content or body stage, and the conclusion stage. Pre- teaching vocabulary taught by the lecturer in every stage aimed to ease the students to comprehend the presentation step by step before doing English presentation in front of the class as the public speaking assignment. The data collection techniques in this research are observation and practice assessment. The result of this research shows that pre-teaching vocabulary method taught in the class for the first semester students significantly enhance the ability of student’s English public speaking in presentation assignment. Students are more confident enough to perform English presentation in front of the class because the topic assigned by the lecturer has been clearly explained and the students are easier to join words by words or phrase by phrase into a short presentation.